Teaching Clinical Reasoning and Critical Thinking in Psychology Graduate Courses: A Systematic Review - Elbir, Tugce; Cammeo, Catia; Cavallini, Francesca; Marchetti, Antonella; Massaro, Davide (Ricerche di Psicologia - Open Access, 2024)
Introduction: There are many studies and reviews that investigate the most functional ways of explicitly teaching clinical reasoning skills in more traditionally healthcare areas such as medicine and nursing, hypothesizing that reducing the gap between theory and practice could guarantee continuity in the quality of care provided to patients. Clinical reasoning and critical thinking are aspects that in clinical practice guide the psychologist in diagnosis and intervention. However, in the psychological field there is a lack of experimental studies that address the issue of direct or explicit teaching of these skills. This systematic review study sought to investigate, via a systematic review, whether there is an association between the teaching methodology and the student’s improvement in their critical analyses and clinical reasoning skills. Statement of the Problem: Despite the importance for clinicians, the interest of researchers and academics is quite recent. Teaching of clinical reasoning is, on the contrary, more common in medicine and nursing sectors. Methodology: Articles published from 2004 until 2023 within PubMed (National Center for Biotechnology Information, NCBI), Web of Science (Core Collection, Clarivate Analytics), Scopus (Elsevier), EBSCO, Scielo, and Psychinfo databases were searched through the following keywords: Critical Thinking - Clinical Reasoning; Problem Based Learning - Case Based Learning; Teaching Methods - Teaching Strategies; Learning Strategies - Clinical Learning; University; Intervention - Training; Psychology; Psychology Students. Results: Theoretical and practical implications to teach clinical reasoning and critical thinking in the psychological field were discussed, including recommendations for designing researches aimed at investigating the impact of the different methodologies, as well as the possibility of including education in critical thinking within the different levels of training dedicated to psychologists. Conclusion: The collected studies presented methodologies that, although different, significantly promoted the improvement of critical thinking in university students, demonstrating that it is “possible” to transfer this complex skill.